Arctic amplification enhanced by latent energy transport of atmospheric planetary waves. (11th May 2016) - Graversen, Rune G.; Burtu, Mattias
Abstract : The atmospheric northward energy transport plays a crucial role for the Arctic climate; this transport brings to the Arctic an amount of energy comparable to that provided directly by the sun. The transport is accomplished by atmospheric waves–for instance large‐scale planetary waves and meso‐scale cyclones–and the zonal‐mean circulation. These different components of the energy transport impact the Arctic climate differently. A split of the transport into stationary and transient waves constitutes a traditional way of decomposing the transport. However this procedure does not take into account the transport accomplished separately by the planetary and synoptic‐scale waves. Here a Fourier decomposition is applied, which decomposes the transport with respect to zonal wave numbers. Reanalysis and model data reveal that the planetary waves impact Arctic temperatures much more than do synoptic‐scale waves. In addition the latent transport by these waves affects the Arctic climate more than does the dry‐static part. Finally, the EC‐Earth model suggests that changes of the energy transport over the twentyfirst century will contribute to Arctic warming, despite the fact that in this model the total energy transport to the Arctic will decrease. This apparent contradictory result is due to the cooling induced by a decrease of the dry‐static transport by planetary waves being more than compensated for by a warming caused by the latent counterpart.